If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-(2x+3)=-6(x+9)
We move all terms to the left:
2-(2x+3)-(-6(x+9))=0
We get rid of parentheses
-2x-(-6(x+9))-3+2=0
We calculate terms in parentheses: -(-6(x+9)), so:We add all the numbers together, and all the variables
-6(x+9)
We multiply parentheses
-6x-54
Back to the equation:
-(-6x-54)
-2x-(-6x-54)-1=0
We get rid of parentheses
-2x+6x+54-1=0
We add all the numbers together, and all the variables
4x+53=0
We move all terms containing x to the left, all other terms to the right
4x=-53
x=-53/4
x=-13+1/4
| 16x=108 | | -6(1-3k)+4=-10 | | -6(2y-3)-9=-15 | | -6(1-3k+4=-10 | | z^2=4z-12=0 | | 28°x+50°+134°=180° | | 2x+1-13(2)=0 | | 5b-5(3b-2)=70 | | -2x+8-25=-9 | | 5(3x-12)=12-3(-x+8) | | 3x^2+11=254 | | x+2.7-2.48=3.368 | | 28x+50°+134°=180° | | -2x+7-6(x-1)=6x-(1x-5)+6 | | -12.4=0.5k+5.7k | | 10x+6x=194.88 | | 7(y-3)=3y+3 | | -2r/8=20/24 | | -1.62=2.4x-5.1x | | -5y-8y=0 | | 4(0.5)f-(0.25)=6+f | | 8.66=-4.4n+4.4-1.9 | | 2+4(n-1)=28-n | | -6(t+1)-t-10=-7(t+3)+5 | | 4a^2+2a-11=-4 | | 5v+6v=0 | | -22p-6(6-5p)=4(p-6)-12 | | 8y+3-2y=9 | | 1+6n-4=-15 | | 2^3x5-8=1 | | -4-3(6x-7)=38+3x | | 8x—10(3-x)=42 |